Information in war : military innovation, battle networks, and the future of artificial intelligence - Jensen, Benjamin M.; Whyte, Christopher, 1988-; Cuomo, Scott (Georgetown University Press, 2022)
"Advances in Artificial Intelligence (AI) will likely revolutionize human affairs in the coming decades. How will military organizations innovate and adapt to this AI revolution? The stakes are high. Military organizations that best integrate AI stand poised to generate significant advantages over their rivals. Those that fail could find themselves irrelevant on future battlefields. Understanding the extent to which AI will change the character of warfare and strategic competition requires a deeper understanding of the relationship between information, organizational dynamics, and military power. To assess how militaries may adopt AI, and where they may go wrong, Benjamin Jensen, Christopher Whyte, and Scott Cuomo offer a conceptual framework and analyze past examples of successes and failures in innovation with military information technologies. Their comparative historical case studies include radar, the switch to early computers in air-defense coordination, battle networks in the Revolution in Military Affairs, and remotely piloted aerial vehicles. The cases demonstrate that the discovery of new technology does not ensure innovation. They identify obstacles to military innovation and suggest how they can be overcome. "Information in War" concludes by sketching four hypothetical outcomes in the US military's adoption of AI by 2040"--